2017
DOI: 10.1136/gutjnl-2016-313060
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of patients with steroid-refractory acute severe UC treated with ciclosporin or infliximab

Abstract: EudraCT: 2006-005299-42; ClinicalTrials.gouv number: NCT00542152; post-results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
99
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(103 citation statements)
references
References 21 publications
2
99
0
2
Order By: Relevance
“…We used cyclosporine/infliximab in only 28 of 207 (14%) patients due to prohibitive costs, with similar use in left-sided and extensive colitis (10/74 vs 18/133, P = ns). In addition, in the long-term follow-up of the CYSIF trial, 19 39 of 115 (34%) patients treated with cyclosporine/infliximab underwent a colectomy within a median follow-up of 5 years, which is similar to our results.…”
Section: Discussionsupporting
confidence: 89%
“…We used cyclosporine/infliximab in only 28 of 207 (14%) patients due to prohibitive costs, with similar use in left-sided and extensive colitis (10/74 vs 18/133, P = ns). In addition, in the long-term follow-up of the CYSIF trial, 19 39 of 115 (34%) patients treated with cyclosporine/infliximab underwent a colectomy within a median follow-up of 5 years, which is similar to our results.…”
Section: Discussionsupporting
confidence: 89%
“…4,19,20 Thirty-two studies [8][9][10] were extracted from these four reviews, 20 included more than 30 patients. [8][9][10]35,36,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] We completed these four systematic reviews by a new PubMed search. We identified 941 citations, of which 844 were excluded, based on the titles or abstracts ( Figure 2).…”
Section: Acute Uc In Population-based Studies (Figure 1)mentioning
confidence: 99%
“…Most of the studies have focussed on patients refractory to IVS, investigating the efficacy of either anti‐TNF agents or calcineurin inhibitors 7–11 . Indeed, very few studies have reported the long‐term outcome of patients with ASUC responding to IVS, especially with respect to the associated maintenance therapy 12,13 .…”
Section: Introductionmentioning
confidence: 99%